Interprofessional Management OF Diplopia AND Visual Health-An Updated Review For Optometrists, Pharmacists, Radiologists, AND Nursing Professionals (The Review of Diabetic Studies, 2024)
Background: Diplopia, or double vision, is a common yet clinically significant visual complaint with diverse ocular, neurological, and systemic etiologies. It may arise from monocular optical disturbances or binocular ocular misalignment, the latter often linked to cranial nerve dysfunction, orbital pathology, or neuromuscular disorders.Aim: This review synthesizes updated evidence on interprofessional approaches to classification, diagnosis, and management of diplopia.Methods: The article evaluates epidemiological data, etiological classifications, diagnostic pathways, and therapeutic options across published clinical studies and specialty guidelines.Results: Binocular diplopia is most frequently associated with microvascular cranial nerve palsy, thyroid eye disease, trauma, and systemic conditions including malignancy and infectious processes such as COVID‑19, with acute cases requiring urgent imaging to exclude life‑threatening pathology. Diagnostic precision relies on structured history, motility testing, and targeted neuroimaging, while management ranges from optical correction and prism therapy to surgical realignment and treatment of underlying disease.Conclusion: Interprofessional collaboration among ophthalmology, neurology, radiology, and rehabilitation services is critical for timely identification of etiologies, reduction of complications, and optimization of functional outcomes for patients with diplopia.